Exploring the Discourse of Subject in Intellectual Property Rights: Communal Rights in Indonesia - Putri, Ria Wierma; Putri, Yunita Maya; Sabatira, Febryani (Simbur Cahaya, 2023)
The objective of this study is to expound on the discourse surrounding the categorization of intellectual property rights (IPR) under public and private international law, which has been a topic of contention among legal experts. Through an in-depth analysis of the IPR debate, including public and private case examples, and the contrast between traditional and communal IPR, this study intends to explore Indonesia's perspective towards IPR and communal rights. Indonesia acknowledges communal rights within IPR and has implemented various legal and policy instruments to safeguard them. It is envisaged that the research findings will advance the ongoing discourse on the classification of IPR under public or private international law, and enhance the comprehension of the legal framework governing IPR in Indonesia. This study will also bring into focus the recognition and protection of communal rights in IPR, which is a crucial subject in modern international law.